Assessment of Risk Factors of Asthma in Health Institutions in Maysan Governorate, Iraq (Medico Legal Update, 2021)
Background: Asthma is a common chronic lung disease in which the airways (bronchi) become inflamedand are abnormally sensitive to certain triggers. Asthma can affect people of all races and ages, and althoughthere is no known cure, there are many ways to control it. The symptoms of asthma include coughing,shortness of breath, wheezing and chest tightness.Materials and Method: This is A case-control study conducted in Consultation Center for Chest andRespiratory Diseases at Al-Sadr Teaching Hospital in Maysan Governorate Data was collected over a periodof five months between the 1st of November 2019 to the 1st of April 2020.Results: The commonest risk factors that had been found causes asthma in cases was family history ofasthma with OR=5.127,CI=(2.77-9.49), upper respiratory tract infection with OR=5.059,CI=(2.29-8.76),active smoker with OR=2.145,CI=(1.18-3.91)Occupational exposure to dust with OR = 4.660,CI= (2.68-8.10), skin allergy with OR =2.77,CI=(1.28-6.03).Conclusion: Significant association was found between (Family history of asthma, upper respiratory tractinfection, active smoking,occupational exposure to dust, chemical, fumes, and gases, allergies and the usedof NSAIDs before the onset of asthma) and asthma in adults in maysan governorate.